AI-Driven Personalized Fitness Coaching with Body Type-Based Workout and Nutrition Plans and Real-Time Exercise Feedback - Ilukpitiya I.M.D.J.R. B; Herath H.M.R. B; Rajakaruna R.H.M.S.A; Herath M.H.S.M; Koliya Pulasinghe; Jenny Krishara, (International Journal of Preventive Medicine and Health (IJPMH), 2025)
In today’s fast-paced world filled with distractions such as work, family, education and other commitments, people often have little time and energy to maintain a healthy lifestyle. Traditional fitness approaches frequently fail to meet the dynamic needs and expectations of modern users, leading to dissatisfaction and disengagement. A main problem of traditional systems is the lack of personalization for diverse users, that also monitors and tracks the workout progression. This study introduces an innovative system that creates a personalized workout and diet plan which aims to engage and motivate the user experience by individual personalization. Through means such as real-time exercise tracking and feedback mechanisms, this mobile fitness application aims to address limitations of traditional fitness approaches, proving fitness experience for users to achieve their health and fitness goals in a convenient and sustainable manner